Proceedings of the 1st International Workshop on Machine Learning and Software Engineering in Symbiosis 2018
DOI: 10.1145/3243127.3243130
|View full text |Cite
|
Sign up to set email alerts
|

Automatically assessing vulnerabilities discovered by compositional analysis

Abstract: Testing is the most widely employed method to find vulnerabilities in real-world software programs. Compositional analysis, based on symbolic execution, is an automated testing method to find vulnerabilities in medium-to large-scale programs consisting of many interacting components. However, existing compositional analysis frameworks do not assess the severity of reported vulnerabilities. In this paper, we present a framework to analyze vulnerabilities discovered by an existing compositional analysis tool and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…We apply FUNDED to five open-source projects that were also evaluated in prior studies [5,18,52,53]. Table V lists the software versions and the number of function-level vulnerabilities.…”
Section: B Evaluation On Large Code Basesmentioning
confidence: 99%
“…We apply FUNDED to five open-source projects that were also evaluated in prior studies [5,18,52,53]. Table V lists the software versions and the number of function-level vulnerabilities.…”
Section: B Evaluation On Large Code Basesmentioning
confidence: 99%
“…Recently, several studies have started to predict CVSS version 3 exploitability metrics including the new Privileges and User Interactions. Ognawala et al [139] fed the features generated by a static analysis tool, Macke [140], to a Random forest model to predict these CVSS version 3 metrics for vulnerable software/components. Later, Chen et al [30] found that many SVs were disclosed on Twitter before on NVD.…”
Section: Exploit Characteristicsmentioning
confidence: 99%
“…Given the overlap, we hereby only describe the main directions and techniques of the Impact-related tasks rather than iterating the details of each study. Overall, a majority of the work has focused on classifying CVSS impact metrics (versions 2 and 3) using three main learning paradigms: single-task [30,50,86,108,139,193,200], multitarget [62,171] and multi-task [65] learning. Instead of developing a separate prediction model for each metric like the single-task approach, multi-target and multi-task approaches only need a single model for all tasks.…”
Section: Confidentiality Integrity Availability and Scopementioning
confidence: 99%
See 1 more Smart Citation
“…2. There may be many other factors [18], such as the degree of connectedness of a function [33] and the distance to an interface such as main function [35], that affect if a vulnerability may be exploited, even if an exploit from main could not be generated. 3.…”
Section: Rq2-vulnerabilitiesmentioning
confidence: 99%